Song and dance over art forms - The Star, Tunku ' Abidin Muhriz (2012)
LAST year I attended a concert staged by the Negri Sembilan Students Association at Universiti Putra Malaysia which included a memorable performance of nine long-barrelled drums, accompanied by a gong and a flautist -singer.